If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 13 = 75 Reorder the terms: 13 + 2x = 75 Solving 13 + 2x = 75 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 2x = 75 + -13 Combine like terms: 13 + -13 = 0 0 + 2x = 75 + -13 2x = 75 + -13 Combine like terms: 75 + -13 = 62 2x = 62 Divide each side by '2'. x = 31 Simplifying x = 31
| 8=0.8*x | | 6t-22=-18+2t | | 0.225*x=45 | | 3r-14=-59+8r | | 2x+3+.5x=180 | | 176=0.5(a+18)11 | | x^3-9x^2+27x-26=0 | | f=.5mw | | 4(x+2)2-(2x-1)2=-5 | | 15-2x=9+x | | 5(5x-9)=34 | | m+37=-4m+6(8m-1) | | 4a-12=5a+6 | | 8+2x-4=6+2(x-1) | | 125/1000= | | 1p=(-1) | | 7x-9=5x+7 | | 0.12*x=3.6 | | -3x*2+24x-48=0 | | 4x^2-33x+8=0 | | -3.2x=40.32 | | 5(u-2)+6=3(6-2u) | | X-2.5Y=3 | | -9+4r=4r+3+-6 | | y=9x-6(2x-1) | | y=2(x+2)-6 | | 0.8x-11=0.3+41 | | 5a=9a-32 | | y=3(x-1) | | 2x-6=3x-18 | | 7(1-5n)+6(1+4n)=13 | | x=7x-78 |